The past, present and future of cactus invasions in South Africa in response to rising atmospheric CO2 and climate change - Venter, Nicolaas (University of the Witwatersrand, Johannesburg, 2023)
Cactaceae originate from the Americas and over the past 250 years have been introduced into South Africa and elsewhere for agricultural and horticultural purposes. Numerous species, including useful taxa, have become important invasive weeds that have serious socio-economic and environmental impacts. Fortunately, management strategies, in particular biological control, have been successful in controlling certain species. However, with rising atmospheric CO2 invasive cacti are likely to pose a renewed threat, whereby evidence shows that cactus species are responsive to CO2 fertilisation, which is likely to increase their vigour, mainly through improved water use efficiency (WUE). Additionally, studies show that plant quality declines with increasing CO2 which in general has negative effects on their arthropod herbivores. This study sought to determine the effect of CO2 on two functionally different invasive cactus species and how they may respond to predicted increases in atmospheric CO2. Opuntia stricta (a succulent shrub) is an obligate CAM photosynthetic species that invades grasslands and savannas across semi-arid to subtropical environments whereas Pereskia aculeata (a scrambling woody vine with well-developed leaves) is a CAM-cycling photosynthetic species that invades forest type habits across subtropical environments. Plants were grown at three CO2 concentrations that represented pre-industrial (sub-ambient - 250 ppm), current (ambient - 400 ppm) and future (elevated - 600 ppm) atmospheric CO2 conditions. Plants were also subject to suboptimal and optimal watering treatments for the duration of the experiments to determine the ameliorative effect of CO2 on productivity in response soil moisture deficits. In addition, an experiment was conducted on O. stricta to test the effects of the three CO2 concentrations on plant quality and the subsequent effect on the fitness and efficacy of its insect biological control agent, Dactylopius opuntiae. Growth and productivity of O. stricta and P. aculeata responded positively to increasing CO2, however the responses varied with CO2 concentration. Increasing atmospheric CO2 concentration from date of introduction to present possibly facilitated O. stricta invasion whereas this was less likely for P. aculeata. In both species WUE increased with increasing CO2. Under suboptimal watering, there was partial amelioration of productivity at 600 ppm CO2, but the plant traits that benefitted varied according to species. Plant quality declined for both species, most notably cladode nitrogen (N) content decreased, and carbon/nitrogen ratios (C/N) increased. When D. opuntiae were exposed to O. stricta grown at elevated CO2 (only tested on well-watered plants), D. opuntiae fitness was reduced which in turn reduced the rates of plant mortality due to the insect damage. Using the WUE results from O. stricta, a mechanistic species distribution model (SDM) created here predicted greater increases in its potential distribution in South Africa under climate change relative to the SDM that did not include WUE as a predictor variable. This suggests that improved WUE under future CO2 concentrations can offset the effect of declining rainfall in certain regions of South Africa. Overall, these results suggest that O. stricta and P. aculeata will show more vigorous growth and are also likely to expand their ranges into regions where rainfall currently limits their distribution. This expanded distribution may be further facilitated by reduced biocontrol agent efficacy as host plant quality declines. These findings suggest that management of these two species and other invasive cacti is likely to become more challenging with increasing atmospheric CO2 and climate change.
A Thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Biological control; CAM photosynthesis; Physiology; Invasive species; Opuntia; UCTD; SDG-13: Climate action